Ornamental kale: A new potential emerging ornamental plant - Dolma, Deachen; Sindhu, S. S.; Dhiman, M. R.; Ankit (Indian Horticulture, 2025)
Ornamental kale (Brassica oleracea L. var. acephala DC.) is an outstanding foliage plant with a vast range of leaf colours and shapes. Plants thrive in lowto-high areas, such as hills and plains. Ornamental kale is more closely related to wild cabbage than most domesticated forms of the vegetable. Owing to its vibrant, multi-shaped leaves and robust cold tolerance, the plant has gained wide popularity as an ornamental potted and cut plant. Ornamental kale is not only decorative but also edible and contains various health-giving compounds, including glucosinolate, phenolic compounds and carotenoids. These compounds are well known for their antioxidant properties, strength and health benefits.